2018
DOI: 10.1088/1361-6501/aababd
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid 2D/3D inspection concept with smart routing optimisation for high throughput, high dynamic range and traceable critical dimension metrology

Abstract: Dimensional surface metrology is required to enable advanced manufacturing process control for products such as large-area electronics, microfluidic structures, and light management films, where performance is determined by micrometre-scale geometry or roughness formed over metre-scale substrates. While able to perform 100% inspection at a low cost, commonly used 2D machine vision systems are insufficient to assess all of the functionally relevant critical dimensions in such 3D products on their own. While cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…approximately 22 µm in sample space per pixel). [47] In the second common type of web inspection, laser scanning, continuous-wave or pulsed laser light is raster scanned over the web repeatedly, and the scattered light is detected by a fast, sensitive single-pixel detector. The detector optical response can be very fast due to its single-pixel readout, so scan speed is usually limited by the mechanical inertia of the laser scan instrument.…”
Section: Beta-ray Transmission Thicknessmentioning
confidence: 99%
“…approximately 22 µm in sample space per pixel). [47] In the second common type of web inspection, laser scanning, continuous-wave or pulsed laser light is raster scanned over the web repeatedly, and the scattered light is detected by a fast, sensitive single-pixel detector. The detector optical response can be very fast due to its single-pixel readout, so scan speed is usually limited by the mechanical inertia of the laser scan instrument.…”
Section: Beta-ray Transmission Thicknessmentioning
confidence: 99%
“…For the present work, both for operational reasons and for professional curiosity, the scanned optical point profilometer route was explored for reference measurements of the 3DRS-II. The reference instrument used was an NPLdeveloped industrial metrology test platform [15], configured as a large-area chromatic confocal microscope (CCM) [16] for the reported work. Townsend et al [5] noted that only 11% of examined literature reported the application of the wider confocal family of measurement techniques to AM surfaces.…”
Section: Reference Instrument For 3drs Calibrationmentioning
confidence: 99%
“…The 3D optical profilometer used was an NPL-developed hybrid 2D/3D measurement platform [11] configured as a large-area Chromatic Confocal Microscope (CCM), capable of measuring the complete areal topography of the plate in one operation. The measured topographies were then used to calculate individual plate feature dimensions.…”
Section: Dimensional Characterisation Of Platementioning
confidence: 99%